The More, the Merrier The Amazing Days of Abby Hayes - Mazer, Anne. (New York, NY : Scholastic, 2002)
Abby's having a party. She decides it's the perfect time to give her room a makeover. Will she finish in time for the party?
"An Apple paperback."
5.
008-012.
410
Accelerated Reader AR
Keywords: Diaries -- Fiction; Girls -- Diaries -- Fiction; Parties -- Fiction